Unusual use of international credit cards to pay for imports for commercial purposes (Revista do Tribunal Regional Federal da 3ª Região, 2013)
It is argued that, although the benign retroactivity of foreign exchange rules that complement blank criminal types is not admissible as a rule, the use of international credit cards to purchase goods for commercial purposes has never been criminally typical - it only constitutes an administrative infraction.
Keywords: Economic criminal law. Currency evasion. International credit card. Importation. Atypicality.; economic criminal law; currency evasion; international credit card; importation; atypicality